Avaliação de atitudes e mudança de comportamento em intervenções educativas para prevenção de arboviroses com uso de dispositivos móveis: Resultados preliminares - Mangueira, Francisco Fernandes Abel (2019)
Background: In Brazil, the National Policy for Dengue Control seeks to incorporate the lessons of national and international experience in dengue control, emphasizing the need for health education activities. Objectives: The objective of this study was to evaluate knowledge, attitudes and behaviours related to the prevention of arboviruses before and after a two-month educational intervention using a learning platform on mobile devices. Methods: This quasi-experimental study corresponds to the first phase of the ZIKAMOB project sponsored as part of the British Council Newton Fund. Results: Thirty of the 93 respondents were first-year undergraduate university students (36.7% male) and 63 were military officers (84.1% male). The pattern of attitudes and behaviour was very similar in the both groups before the intervention. The students changed their attitudes and behaviour (p=0.032) in relation to their engagements in actions for the prevention of arboviral diseases and several other activities related to house inspections and the precautions with water tanks (p<0.01). However, recycling and surveillance activities were not as effective to change behaviour. Female participants showed more motivation to participate in preventive activities; living alone and working are barriers to develop these activities and individuals who already perform selective waste collection and have the habit cultivating gardens demonstrate positive attitude and behaviour towards actions for the prevention of arboviral diseases. Conclusion: Mobile learning and behaviour change theories might be successful to develop school-based and community-based interventions to avoid arboviruses. These outcomes need to be confirmed in broader future studies.